The likelihood of choosing alternative source of collagen among consumers: logistic regression approach - Duasa, Jarita; Muhamad Husin, Afifah (RMP Publication, 2020)
: Collagen is the main structural protein of hard and soft tissues in animals and human body. It can maintain the biological and structural integrity of extracellular matrix and also provides physical support to tissues. Collagen is much needed nowadays because there are some factors that can deplete the level of collagen within the body. High sugar consumption, exposure to ultraviolet in the sunlight, smoking, genetic changes, autoimmune disorder and aging process are the common factors that can damage the collagen within the human body. Collagen is used in pharmaceutical industries, tissues engineering, food industry, cosmetics, biomedical industry and medical field. The sources of collagens and gelatins are recently being questioned particularly among the Muslim users on the status of syariah permissible (halal). This is because the raw materials used in its manufacture could be sourced from porcine or non-halal slaughtered animals. There are growing concerns regarding the transfer of diseases from animal sources of collagen to human users and the halal issue on the sources and manufacturing processes of it. Though currently collagen can be extracted from marine life, the sources are very limited and this is the main reason why an alternative source is being explored in the current study. The current study provides an alternative source to the available collagen market using recombinant collagen-like protein. The present study aims to analyze the factors that contribute to the probability of using this alternative source of collagen among consumers. Using survey data collected within the area of Wilayah Persekutuan and Selangor (Klang Valley), the data then are tested empirically using Logistic regression. The study finds that the probability consumers opt for the alternative source of collagen is significantly determined by age of consumers and the level of their incomes. The likelihood of the consumers to opt for this alternative source of collagen is higher among elderly and lower income consumers.